Oxidation of [3]naphthylenes to cations and dications converts local paratropicity into global diatropicity - Abel Cárdenas; Zexin Jin; Yong Ni; Jishan Wu; Yan Xia; Francisco Javier Ramírez; Juan Casado (Beilstein Journal of Organic Chemistry)
Oxidized states of polycyclic aromatic hydrocarbons are of importance as they represent charged conductive species in organic semiconductor substrates. In this work, we investigated the properties of radical cations and dications of linear and angular [3]naphthylenes, consisting of fused aromatic naphthalenoid and antiaromatic cyclobutadienoid moieties and containing different degrees of paratropicity. Electronic absorption and vibrational Raman spectroscopies were used to describe the more relevant bonding changes. Stretching force constants were evaluated to monitor the aromatic–antiaromatic alternation pattern upon oxidation. They showed us that the dication of linear [3]naphthylene became an overall global π-electron delocalized molecule. This result was supported by nucleus independent chemical shift (NICS) calculations and anisotropy of the current induced density (ACID) plots, as they evidenced the presence of a perimetral diatropic global ring current upon oxidation.